2023
DOI: 10.3389/fneur.2023.1142084
|View full text |Cite
|
Sign up to set email alerts
|

Fasting blood glucose-to-glycated hemoglobin ratio for evaluating clinical outcomes in patients with ischemic stroke

Abstract: BackgroundStress hyperglycemia frequently occurs in patients with acute ischemic stroke (AIS). The influence of stress hyperglycemia on the outcomes of patients with AIS remains ambiguous.MethodsData from our institution on patients with AIS between June 2020 and June 2021 were retrospectively analyzed. The severity of the stroke was assessed using the National Institutes of Health Stroke Scale (NIHSS) at admission, and the primary endpoint was functional outcomes. Stress hyperglycemia was measured by the gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Moreover, it is worth highlighting that, in the present study, despite less than 40% of the included subjects having diabetes diagnosis before admission, the imbalance between acute and chronic glycemic control continued to be an outcome-predictive factor during follow-up. A very recent study [ 22 ], in this case evaluating the FBG/ HbA1c ratio and not ACR, observed this ratio to be associated with more severe AIS. Specifically, the glucose-to-HbA1c ratio was associated with functional outcomes in patients without diabetes but not in patients with diabetes.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, it is worth highlighting that, in the present study, despite less than 40% of the included subjects having diabetes diagnosis before admission, the imbalance between acute and chronic glycemic control continued to be an outcome-predictive factor during follow-up. A very recent study [ 22 ], in this case evaluating the FBG/ HbA1c ratio and not ACR, observed this ratio to be associated with more severe AIS. Specifically, the glucose-to-HbA1c ratio was associated with functional outcomes in patients without diabetes but not in patients with diabetes.…”
Section: Discussionmentioning
confidence: 74%